Infinity kings - Silvera, Adam, 1990- (Silvera, Adam, 1990- Infinity cycle, 2024)
This electrifying conclusion to the Infinity Cycle finds Emil, the Infinity Son, and Brighton, the Infinity Reaper, facing off in an epic battle that threatens to destroy them both and everyone they love.